Investigation of dynamic mechanical properties of the additively manufactured continuous carbon fiber composites - Zheng, Minqiang (Nanyang Technological University, 2022)
Advancement in multi-material fused deposition modeling has gained great attention in its capability to fabricate fiber-reinforced composites. Even though some research has been done on additively manufactured carbon fiber composites to explore their mechanical properties and viability of replacing conventional manufacturing processes. But research mostly focused on the static properties of the material such as flexural strength, tensile strength, and impact strength. But not much work was put into discovering the dynamic properties of such as fatigue and creep of the material. These properties are crucial for parts that undergo a constant cyclic loading process, one great example of such application is the use of additively manufactured carbon fiber composites in creating prosthetic limbs, taking advantage of both the customizability of AM process and the superb properties of carbon fiber composite, allowing the designer to make full use of this technology. The main goal of this report is to investigate the fatigue properties of the additively manufactured continuous carbon fiber composites. In the process, tensile properties will be explored to obtain the required parameter for fatigue tests. The design of specimens and tests will be in accordance with ASTM standards. Specimens used in this report will be fabricated with Markforged X7 Industrial Composite 3D Printer using carbon fiber and onyx available from Markforged.